MEKANISME BEKERJANYA MODAL SOSIAL DALAM MENGEMBANGAN DESA WISATA CANDRAN SEBAGAI SARANA PENINGKATAN PENDAPATAN MASYARAKAT (Studi di Desa Wisata Candran, Desa Kebonagung, Kecamatan Imogiri, Kabupaten Bantul) - , Idah Rosida ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The emergence of social capital in the society after the earthquake hitting Bantul and its vicinity in 2006 is an interesting phenomenon to be studied. Social capital becomes a stimulator of the society in Candran Quarter, Mandingan Hamlet, Kebun Agung Village, Bantul, Yogyakarta Special Region where is one of the earthquake victimsâ regions to immediately resurrect from the downturn after the earthquake. This study discusses about the working mechanism of social capital in developing Candran village tourism as a means of increasing society revenue. The purpose of this study is to identify the factors that influence the emergence of social capital in the Candran village tourism, to analyze the working mechanism of social capital in the society in Candran village tourism, and to see the impact of its use of the increasing society revenue. This study is a descriptive qualitative research. The approach used in this study is a case study. This study is using observation, interview, and documentation techniques in collecting data. The result shows that social capital in the society in Candran village tourism emerges slowly and gradually from the society, so it brings up strong society participation. The cause of emergence is influenced by several factors, such as: 1) territorial factor because of the sense in sharing anotherâs trials and tribulations among the victims after the earthquake , 2) economic factor in which the society want to increase their revenue, 3) social factor in which the society want to solve their problems together, 4) cultural factor in which the society want retain Javanese culture and agricultural tradition that has faded. The emergence of social capital is strengthened by: 1) the existence of Museum Tani Jawa Indonesia as an institution that organizing it, 2) the existence of actor who move as an initiator in forming a tourism village, and 3) the existence of various motivations that encourage the society to develop a Candran village tourism. Types of social capital that exist and work in the development of the Candran village tourism are: 1) high trust toward others, especially people who are members of the Candran village tourism manager, 2) active participation in the society, 3) existence of a reciprocal attitude of kindness (reciprocity) among the society even to outsiders, 4) having an extensive and strong partnerships network, both internal network and external network, 5) having the consistency of the values and norms which are relatively stable. All these types of social capital grow and develop until these mobilize the society to develop Candran village tourism and to bring domestic and foreign tourists to there. Based on the result of the analysis, the constraints that undermine social capital must be anticipated by any parties to hold training, mentoring, and assisting so that social capital which exists in the society in Candran village tourism still grows and develops.